Clumped isotope evidence for Early Jurassic extreme polar warmth and high climate sensitivity - T. Letulle; G. Suan; M. Daëron; M. Rogov; C. Lécuyer; A. Vinçon-Laugier; B. Reynard; G. Montagnac; O. Lutikov; J. Schlögl (Climate of the Past, 2022)
Periods of high atmospheric CO 2 levels during the Cretaceous–early Paleogene ( ∼ 140 to 34 Myr ago) were marked by very high polar temperatures and reduced latitudinal gradients relative to the Holocene. These features represent a challenge for most climate models, implying either higher-than-predicted climate sensitivity to atmospheric CO 2 or systematic biases or misinterpretations in proxy data. Here, we present a reconstruction of marine temperatures at polar ( > 80 ∘ ) and middle ( ∼ 40 ∘ ) paleolatitudes during the Early Jurassic ( ∼ 180 Myr ago) based on the clumped isotope ( Δ 47 ) and oxygen isotope ( δ 18 O c ) analyses of shallow buried pristine mollusc shells. Reconstructed calcification temperatures range from ∼ 8 to ∼ 18 ∘ C in the Toarcian Arctic and from ∼ 24 to ∼ 28 ∘ C in Pliensbachian mid-paleolatitudes. These polar temperatures were ∼ 10–20 ∘ C higher than present along with reduced latitudinal gradients. Reconstructed seawater oxygen isotope values ( δ 18 O w ) of − 1.5 ‰ to 0.5 ‰ VSMOW and of − 5 ‰ to − 2.5 ‰ VSMOW at middle and polar paleolatitudes, respectively, point to a significant freshwater contribution in Arctic regions. These data highlight the risk of assuming the same δ 18 O sw value for δ 18 O-derived temperature from different oceanic regions. These findings provide critical new constraints for model simulations of Jurassic temperatures and δ 18 O sw values and suggest that high climate sensitivity has been a hallmark of greenhouse climates for at least 180 Myr .